Spontaneom Spinal Extradural Hematoma - Benedek, Pedro; Estable, Miguel; Medoc, Juan; Purriel, Juan (Cirugía del Uruguay, 1980)
The first case .in the uruguayan literature. of a spontaneous spina' epidural hematoma is presented. The clínica! course is described, with sudden onset of severe lumbar pain, acute paraplegia and. bladder and bowel dysfunction.